Belt and Road Initiative Impact on Bilateral Trade Flows: Evidence from 123 Partner Countries through a Panel EGLS Model - Amani, Ismail; Kaci, Nadjet (Latin American Journal of Trade Policy, 2022)
This study aims to assess Belt and Road Initiative impact on bilateral trade between China and the partner countries. Thus, a Panel EGLS gravity model on data of 123 countries from 2012 to 2019 has been elaborated including standard gravity model variables as geographical and socio-cultural distance, local income. This model has been enhanced by introducing a dummy variable representing the membership of the partner country in the BRI and/or in WTO. Results show that standard gravity variables have their usual effects, a negative impact of distance while local incomes and sharing a common language have a positive effect. WTO membership has a positive impact too on bilateral trade between the considered countries. BRI also has a positive impact on bilateral trade between China and partner countries, hence its benefits for both. This positive impact is higher in BRI main road’s regions, Middle East, Europe, South and East Asia, while it lower in other regions as Latin America and North Africa.